2005
DOI: 10.1124/mol.105.015479
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide-Dependent Reduction in Soluble Guanylate Cyclase Functionality Accounts for Early Lipopolysaccharide-Induced Changes in Vascular Reactivity

Abstract: We investigated the role of soluble guanylate cyclase in lipopolysaccharide-induced hyporesponsiveness to phenylephrine. The effects of phenylephrine on the blood pressure of female Wistar rats were evaluated at 2, 8, and 24 h after lipopolysaccharide injection (12.5 mg/kg i.p.). Vasoconstrictive responses to phenylephrine were reduced 40 to 50% in all time periods. Methylene blue, a soluble guanylate cyclase inhibitor (15 mol/kg i.v.) restored the reactivity to phenylephrine in animals injected with lipopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 40 publications
(56 reference statements)
1
25
0
4
Order By: Relevance
“…Observing the other 55 studies we can find: 1) one study (1.67%) based on evidences through metanalysis of literature [13]; 2) seven review articles (11.67%) [4,14,23]. The other bibliographical citations in number of 44 (73.33%) are distributed as case reports (great majority) [24][25][26][27][28][29][30][31][32][33][34][35][36], letters [37][38][39][40][41][42][43][44], technical aspects of the MB use [45][46][47][48][49][50] and other studies involving risk [51,52], the VS incidence in the "off pump" CABG and the possibility of MB use in anaphylaxis and anaphylactic shock [53], also a proposal of the author of this text ( Figure 4) [54][55][56][57][58]. The presented numbers, surely, are not totally compatible with the total of publications, but it is possible to assume that this imprecision does not affect the general vision of the problem.…”
Section: Resultsmentioning
confidence: 99%
“…Observing the other 55 studies we can find: 1) one study (1.67%) based on evidences through metanalysis of literature [13]; 2) seven review articles (11.67%) [4,14,23]. The other bibliographical citations in number of 44 (73.33%) are distributed as case reports (great majority) [24][25][26][27][28][29][30][31][32][33][34][35][36], letters [37][38][39][40][41][42][43][44], technical aspects of the MB use [45][46][47][48][49][50] and other studies involving risk [51,52], the VS incidence in the "off pump" CABG and the possibility of MB use in anaphylaxis and anaphylactic shock [53], also a proposal of the author of this text ( Figure 4) [54][55][56][57][58]. The presented numbers, surely, are not totally compatible with the total of publications, but it is possible to assume that this imprecision does not affect the general vision of the problem.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a brilliant doctoral thesis was defended at the Federal University of Florianopolis (which has already been published by Fernandes et al [40] ) and brings some very important data to attempt to answer that question.…”
Section: The Inhibition Of Guanylate Cyclase By Methylene Blue As Thementioning
confidence: 99%
“…Previous work from our laboratory has shown that ODQ failed to restore vascular responsiveness in response to phenylephrine when administered early (8 h) after lipopolysaccharide (da Silva-Santos et al, 2002). This failure of ODQ to restore vascular responsiveness has been shown to depend, at least in part, on a reduction in the sGC protein content (Fernandes et al, 2006).…”
mentioning
confidence: 97%
“…The mortality rate was recorded over a 5-day period. Doses of MB and ODQ were chosen based on our own experience (da Silva-Santos et al, 2002;Fernandes et al, 2006) and from other published studies (Keaney et al, 1994;Zacharowski et al, 2001).…”
Section: Experimental Protocolsmentioning
confidence: 99%